Optimization of pretreatments and sugar concentration of strawberry candy - Jadhav, Puskraj; Patil, Shital A; Udachan, Irrana; Madavi , Arvind B; Lokhande, Siddharth M (Journal of Postharvest Technology, 2022)
The aim of the research was to develop a self-stable dehydrated strawberry product using different  pretreatment and sugar solutions on the characteristics of strawberry candy. Whole strawberry  candy was prepared using ripe strawberry fruits of the Sweet Charlie cultivars. The strawberries  were washed in running tap water and blanched in hot water for 2 minutes. Pretreatments were  given using 3 different combinations of chemicals, among which treatment C (2% Ethyl Oleate + 1%  Citric acid) was selected based on the color and maximum ascorbic acid retention. The strawberries  were then immersed in sugar solutions with concentrations of 40%, 50%, 60%, and 70% for 3-5  hours. The product obtained by osmotic dehydration is more stable during storage due to the low  water activity imparted by solid gain and water loss. The concentration of sugar syrup 700B with a  dipping time of 3 hours at 45°C was found to be suitable based on the solid gain-water loss ratio.
Keywords: Strawberry Candy; Pretreatments,; , osmotic dehydration; Sugar solution; Nutritional composition; Organoleptic quality.